Evolution of vascular plants through redeployment of ancient developmental regulators - Lu, Kuan-Ju (Proc Natl Acad Sci U S A, 2020)
Vascular plants provide most of the biomass, food, and feed on earth, yet the molecular innovations that led to the evolution of their conductive tissues are unknown. Here, we reveal the evolutionary trajectory for the heterodimeric TMO5/LHW transcription factor complex, which is rate-limiting for vascular cell proliferation in Arabidopsis thaliana. Both regulators have origins predating vascular tissue emergence, and even terrestrialization. We further show that TMO5 evolved its modern function, including dimerization with LHW, at the origin of land plants. A second innovation in LHW, coinciding with vascular plant emergence, conditioned obligate heterodimerization and generated the critical function in vascular development in Arabidopsis. In summary, our results suggest that the division potential of vascular cells may have been an important factor contributing to the evolution of vascular plants.